Surfactant‐Mediated Conformal Overgrowth of Core–Shell Metal–Organic Framework Materials with Mismatched Topologies. Issue 41 (7th September 2015) - Zhuang, Jia; Chou, Lien‐Yang; Sneed, Brian T.; Cao, Yingze; Hu, Pan; Feng, Lin; Tsung, Chia‐Kuang
Abstract : Fracture‐free and conformal Pd–UiO‐66@ZIF‐8 core–shell metal–organic framework material is synthesized by a surfactant‐mediated method. The hierarchical nanoporous material exhibits great size‐selective hydrogenation catalysis and demonstrates potentials for many different applications.